Readiness to Implement Inclusive Education in Muhammadiyah Elementary Schools of Yogyakarta - Ratna Sari; Muhammad Nurul Ikhsan Saleh (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2020)
This research aims to find out the readiness of Muhammadiyah elementary schools in implementing inclusive education in the schools. School readiness clearly marks the path for Muhammadiyah elementary schools in organizing inclusive education. Through a case study methodology with a purposive sampling technique, this research investigates the readiness of four Muhammadiyah elementary schools. The data were collected by an in-depth interview and observation and would be analyzed by thematic analysis method. This research provides worthy indicators of school readiness in executing inclusive education. This study indicates that two out of the four Muhammadiyah elementary schools observed, have not reached the required level of readiness to implement inclusive schools based on the indicators of the school readiness, whereas the other two schools are more prepared to fully run the inclusive education program. This study enhances elementary schools to implement inclusive education by meeting five required indicators: 1) Perception of school stakeholders; 2) Curriculum and teaching and learning activities; 3) Educational staffs; 4) Facilities, infrastructure, and funding; 5) Relationship between community and school. The implementation of inclusive education in elementary schools under the Muhammadiyah institution as one of the biggest Islamic organizations in Indonesia would build a positive perception for all teachers, students’ parents, and school communities.